The prevalence of the Val66Met polymorphism in musicians: Possible evidence for compensatory neuroplasticity from a pilot study. - Tara L Henechowicz; Joyce L Chen; Leonardo G Cohen; Michael H Thaut (PLoS ONE)
The study compared the prevalence of the Val66Met Brain-derived Neurotrophic Factor single nucleotide polymorphism (rs6265) in a sample of musicians (N = 50) to an ethnically matched general population sample from the 1000 Human Genome Project (N = 424). Met-carriers of the polymorphism (Val/Met and Met/Met genotypes) are typically present in 25-30% of the general population and have associated deficits in motor learning and plasticity. Many studies have assessed the benefits of long-term music training for neuroplasticity and motor learning. This study takes a unique genetic approach investigating if the prevalence of the Val66Met BDNF polymorphism, which negatively affects motor learning, is significantly different in musicians from the general population. Our genotype and allele frequency analyses revealed that the distribution of the Val66Met polymorphism was not significantly different in musicians versus the general population (p = 0.6447 for genotype analysis and p = 0.8513 allele analysis). In the Musician sample (N = 50), the prevalence of the Val/Met genotype was 40% and the prevalence of the Met/Met genotype was 2%. In the 1000 Human Genome Project subset (N = 424), the prevalence of Val/Met was 33.25% and the Met/Met genotype prevalence was 4%. Therefore, musicians do exist with the Val66Met polymorphism and the characteristics of long-term music training may compensate for genetic predisposition to motor learning deficits. Since the polymorphism has significant implications for stroke rehabilitation, future studies may consider the implications of the polymorphism in music-based interventions such as Neurologic Music Therapy.